PERSPEKTIF FAKTOR KEUANGAN DENGAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Deranika Ratna Kristiana; Ivana Oktarina Sopacua; Cahyo Indraswono (Universitas Widyatama, 2021)
This research aims to determine the financial factors that can influence punctuality in submitting financial reports on the consumption industry companies listed on the Indonesian Stock Exchange for four years (2017-2020). The financial factor used in this research is an independent variable: profitability projected with ROA, leverage to determine the debt ratio amount toward equity, and managerial ownership to determine how much the share ownership management influences the decision-making. The research sample consisted of 29 companies of the consumption industry selected using purposive sampling with specific criteria. The data analysis applies the analysis of regression panel data. This research result showed that ROA was not negatively influenced by punctuality in submitting the financial report, and managerial ownership influences positively and significantly on punctuality in submitting the financial report.